The Role of Government in Economic Development: A Case Study of the Tourism Industry in Australia - Lyu, Jialin (Transactions on Economics, Business and Management Research, 2024)
This paper has examined the economic impact brought by tourism in Australia through highlighting its significant contribution to GDP and other aspects of Australian economy. In this context, the crucial role played by government support in fostering tourism development through financial assistance and long-term strategic planning can be highlighted. Then the future challenges faced by the Australian tourism sector have been explored ranging from ongoing health threat caused by global health crisis, climate change and changing consumer preferences. Through such a comprehensive review of relevant literature and data, the importance of sustainable tourism practices and adaptive strategies to ensure the sustainable growth of this industry have been discussed which can drive cultural enrichment. The reason why this research is crucial is that it is helpful for the long-term strategic development of the Australian Tourism industry. Besides, it can also offer guidance for other countries whose supporting industries are also impacted by sudden events like COVID-19.